Sustainability of Interior Design materials for 5* Hotels in the UAE - Sadeghi Esfahani, Golnaz (2020)
The study aimed to gain insights from the interior designers regarding the implementation of sustainability in the luxury five-star hotels' interior design in the context of the UAE. To achieve this primary aim, the following objectives were outlined: to evaluate the implementation of sustainability in the UAE’s five-star hotels’ interior design; to analyse how LEED guidelines are incorporated into the hotels' interior design in the UAE; to assess the challenges in integrating sustainability in luxury hotel interiors in the UAE; to examine the sustainable choice of materials by the interior designers for the UAE hotels’ interior design. For this, a qualitative approach was selected, and semi-structured interviews were carried out with six specialist interior designers. Using a template thematic analysis approach, it was identified that there is a disconnect between sustainability and luxury, but that integrating sustainability in the UAE’s hotels is encouraged. LEEDs guidelines are only used when the project itself specifies the usage. However, some participants try to incorporate the guidelines during their choice of materials. In addition, the most significant challenges to incorporating sustainability were identified as being related to cost and client resistance. The study also developed an understanding of the commonly used materials in interior design and their sustainability ratings based on the participants. The implications of the study are discussed, and some recommendations are provided.